HINDU TEMPLE WOMEN OF THE CHOLA PERIOD IN SOUTH INDIA - LESLIE C. ORR (Faculty of Religious Studies McGill University, Montreal, 1993)
This study examines the situation and activities of Hindu temple women (davadasls) in the 9th-13th centuries, as revealed in Tamil inscriptions. These temple women, unlike Lheir male counterparts or the devadasls of more recent times, were not primarily itiantified as tp.mple servants, with professional expertise or ritual responsibilities, but were instead defined with reference to a particular status, predicated on relationship with a temple. This relationship was secured through the donations that temple women made to temples. In the course of the Chola period, the status of "temple woman" became increasingly well-defined and the num- bers of temple women increased, while other types of women disappeared from public view. Temple women's strengthening links with--but marginal positions in--the temple are ana- lyzed in this study with reference to the changes that occurred during this period in the structure of the temple and in the temple's position within the social environment .